Comparison of prospective head motion correction with NMR field probes and an optical tracking system. Issue 1 (29th July 2018) - Eschelbach, Martin; Aghaeifar, Ali; Bause, Jonas; Handwerker, Jonas; Anders, Jens; Engel, Eva‐Maria; Thielscher, Axel; Scheffler, Klaus
Abstract : Purpose: The aim of this study was to compare prospective head motion correction and motion tracking abilities of two tracking systems: Active NMR field probes and a Moiré phase tracking camera system using an optical marker. Methods: Both tracking systems were used simultaneously on human subjects. The prospective head motion correction was compared in an MP2RAGE and a gradient echo sequence. In addition, the motion tracking trajectories for three subjects were compared against each other and their correlation and deviations were analyzed. Results: With both tracking systems motion artifacts were visibly reduced. The precision of the field probe system was on the order of 50 µm for translations and 0.03° for rotations while the camera's was approximately 5 µm and 0.007°. The comparison of the measured trajectories showed close correlation and an average absolute deviation below 500 µm and 0.5°. Conclusion: This study presents the first in vivo comparison between NMR field probes and Moiré phase tracking. For the gradient echo images, the field probes had a similar motion correction performance as the optical tracking system. For the MP2RAGE measurement, however, the camera yielded better results. Still, both tracking systems substantially decreased image artifacts in the presence of subject motion. Thus, the motion tracking modality should be chosen according to the specific requirements of the experiment while considering the desired image resolution, refresh rate, and head coil constraints.